La comunicación asertiva y su incidencia en el aprendizaje colaborativo de los estudiantes de la U.E Lenin cantón Quevedo - Chacha Fajardo, Leyda Rosybel (2025)
Assertive communication has been recognized as an essential element to strengthen collaborative learning in various educational systems; in the educational context of the Quevedo canton, province of Los Ríos, educational dynamics reflect the cultural and social characteristics of the region, therefore the research was carried out with the objective of determining the incidence that exists between assertive communication and collaborative learning of students in the Educational Unit "Lenin el Cantón Quevedo. Where a mixed type methodology was implemented with a correlational approach of a basic nature, using a sample of 43 subjects, corresponding to teachers, directors and students of a specific parallel of the unit, as a study technique a Likert scale survey was used. The results of the study showed that there is a direct relationship between assertive communication and collaborative learning, since students who express their ideas clearly and respectfully participate more actively in group dynamics.